Review of Digital Literacy for Educational Advancement - Khoyyinuddin, Muhammad; Rahmah, Manzilatur; Fathul, Sri Wahyu Hidayati Umi (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
Digital Literacy has a strategic role in advancing education. This research aims to conduct a review of Digital Literacy for Educational Progress. This research uses qualitative methods. The approach to this research uses descriptive and literature studies. Data was obtained from reference literature on the open-access platform. This research shows that Digital Literacy plays a vital role in educational progress. The government and education stakeholders need to pay attention to digital literacy, which is beneficial for educational progress.